Management of desmoid tumours: A large national database of familial adenomatous patients shows a link to colectomy modalities and low efficacy of medical treatments. Issue 5 (August 2017) - Walter, T; Zhenzhen Wang, C; Guillaud, O; Cotte, E; Pasquer, A; Vinet, O; Poncet, G; Ponchon, T; Saurin, J-C
Background: Desmoid tumours represent a major complication of familial adenomatous polyposis. Our aims were to study the factors associated with the development of desmoid tumours in familial adenomatous polyposis patients, and to describe presentation and management of desmoid tumours. Methods and patients: We reviewed all patients with familial adenomatous polyposis followed at our institution between 1965–2013, with either identified adenomatous polyposis coli gene mutation, or a personal and family history suggesting adenomatous polyposis coli-related polyposis. Response to treatment of desmoid tumours was assessed by Response Evaluation Criteria In Solid Tumor (RECIST) criteria. Results: A total of 180 patients with familial adenomatous polyposis were included with a median follow-up of 19 years since diagnosis. Thirty-one (17%) patients developed 58 desmoid tumours, a median (range) 4.7 (0.8–41.6) years after their diagnosis of familial adenomatous polyposis. The only factor significantly associated with occurrence of desmoid tumours was the type of surgery: 12 (12%) desmoid tumours in 104 patients treated by colectomy, versus 19 (25%) desmoid tumours in 76 patients treated by proctocolectomy, p  = 0.027. The localisation of desmoid tumours was: mesenteric ( n  = 25), abdominal wall ( n  = 30) or extra-abdominal ( n  = 3). Nineteen patients underwent 36 surgical procedures for desmoid tumours. Recurrence occurred in 26 (72%) cases and the recurrence-free survival was 2.6 (95% confidence interval (CI), 0.2–5.9) years. Thirteen patients received 27 medical treatments over a median 14 months. Objective response was observed in four (15%) patients and the median progression-free survival was nine (95% CI, 1.1–16.9) months. Conclusion: If confirmed, colectomy (versus proctocolectomy) should be performed in adenomatous polyposis coli-related familial adenomatous polyposis patients to avoid desmoid tumours. We show that there is a high prevalence of post-surgical recurrence and the low efficacy of available medical treatments for desmoid tumours.